Concentration of TNF-Î± in the peritoneal fluid and serum of endometriotic patients - TEDJA DANUDJA OEPOMO (Society for Indonesian Biodiversity, 2006)
The aim of this research was to expose the relation between tumor necrosis factor alpha (TNF-Î±) in the peritoneal fluid and in the serum of endometriosis patients. It was conducted at Dr. Muwardi Hospital Surakarta. Twenty patients undergoing laparoscopic operation because of endometriosis indication (Endometriosis Group), 20 women (aged 23 to 40) who undergo interval sterilization by means of laparoscopic technique. During laparoscopic operation, peritoneal fluid is taken to examine TNF-Î± by ELISA technique. At the same time, the serum isalso taken to examine TNF-Î± by the same technique. The research result indicated that by independent sample t-test, the TNF-Î± concentration in the Endometriosis Group is quite different from the control group (P=0.00). The simple linear regression test shows a strong positive one-way correlative relation between TNF-Î± concentration in the peritoneal fluid and TNF-Î± concentration in the serum in the Endometriosis Group. The research result indicated that the TNF-Î± concentration in the serum can be used as a reflection of endometriosis. A statistical test is done to find the limit value based on sensitivity and specification.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: endometriosis, TNF-Î±, peritoneal fluid, serum.